1997
DOI: 10.1038/sj.bmt.1700658
|View full text |Cite
|
Sign up to set email alerts
|

Results of a pilot study of 40 patients using high-dose therapy with hematopoietic rescue after standard-dose adjuvant therapy for high-risk breast cancer

Abstract: Summary:untreated patients shows little effect of adjuvant therapy in the first 4 years and only a modest statistically significant effect thereafter. 2 Thus, a trend toward a more aggressive The study was designed to determine the toxicity, feasibility, and effectiveness of high-dose cyclophosphamide approach for this subset of patients has occurred in the last years. (6 g/m 2 ), thiotepa (500 mg/m 2 ) and carboplatin (800 mg/m 2 ) (CTCb) with hematopoietic rescue as consoli-The dose intensity hypothesis has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 3 publications
2
13
1
Order By: Relevance
“…These results are significantly better than historical or contemporary data obtained for similar prognosis patients receiving SDC. A number of other phase II trials have also reported encouraging results in high-risk primary disease [61][62][63][64]. ABMTR reported outcomes [43] in high-risk primary disease are consistent with the phase II reports.…”
Section: Hdc For High-risk Primary Breast Cancersupporting
confidence: 81%
“…These results are significantly better than historical or contemporary data obtained for similar prognosis patients receiving SDC. A number of other phase II trials have also reported encouraging results in high-risk primary disease [61][62][63][64]. ABMTR reported outcomes [43] in high-risk primary disease are consistent with the phase II reports.…”
Section: Hdc For High-risk Primary Breast Cancersupporting
confidence: 81%
“…The toxicity appears equivalent to previously published reports in women receiving autotransplants for breast cancer. [11][12][13][14] Although the number of subjects is small, the efficacy of autotransplant in these 13 men with high-risk breast cancer appears similar to results reported in women. 11,12 Outcomes of the patients with metastatic disease were disappointing, however only three patients were available for analysis.…”
Section: Discussionsupporting
confidence: 63%
“…low-up of 36 months the DFS was 84%. Tomás and coworkers 25 recently published their high-dose experience in…”
Section: Treatment Programmentioning
confidence: 99%